2019
DOI: 10.5194/acp-19-6595-2019
|View full text |Cite
|
Sign up to set email alerts
|

High-time-resolution source apportionment of PM<sub>2.5</sub> in Beijing with multiple models

Abstract: Abstract. Beijing has suffered from heavy local emissions as well as regional transport of air pollutants, resulting in severe atmospheric fine-particle (PM2.5) pollution. This study developed a combined method to investigate source types of PM2.5 and its source regions during winter 2016 in Beijing, which include the receptor model (positive matrix factorization, PMF), footprint and an air quality model. The PMF model was performed with high-time-resolution measurements of trace elements, water soluble ions, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 70 publications
5
47
3
Order By: Relevance
“…The strong correlations of WSOC with EC (p < 0.001, r = 0.95) and K (p < 0.001, r = 0.88) in Table S2 suggested that the WSOC in study period was closely related to combustion related sources especially biomass burning [36]. In addition, WSOC exhibited strong correlations with metal species such as As (correlation coefficient as 0.93), Se (0.84), Pb (0.84), Mn (0.88), Fe (0.87), and Zn (0.90), which were widely used as markers for primary and combustion related sources such as coal combustion [64,65], vehicle emission [12,36], and industrial sources [66]. Contributions of vehicle emissions and industrial sources to WSOC have been reported in Tianjin (41%) [67] and Beijing (20%) [17], respectively.…”
Section: Primary Sources Of Wsoc Determined By the Pmf Modelmentioning
confidence: 94%
See 2 more Smart Citations
“…The strong correlations of WSOC with EC (p < 0.001, r = 0.95) and K (p < 0.001, r = 0.88) in Table S2 suggested that the WSOC in study period was closely related to combustion related sources especially biomass burning [36]. In addition, WSOC exhibited strong correlations with metal species such as As (correlation coefficient as 0.93), Se (0.84), Pb (0.84), Mn (0.88), Fe (0.87), and Zn (0.90), which were widely used as markers for primary and combustion related sources such as coal combustion [64,65], vehicle emission [12,36], and industrial sources [66]. Contributions of vehicle emissions and industrial sources to WSOC have been reported in Tianjin (41%) [67] and Beijing (20%) [17], respectively.…”
Section: Primary Sources Of Wsoc Determined By the Pmf Modelmentioning
confidence: 94%
“…In contrast, during pollution episodes, air masses As shown in Figure 4, primary sources were the predominant contributors to WSOC during different periods, accounting for 68% of WSOC on average, including biomass burning (22%), other combustion source (19%), industrial source (17%), coal combustion (7%), and dust (3%). The strong correlations of WSOC with EC (p < 0.001, r = 0.95) and K (p < 0.001, r = 0.88) in Table S2 suggested that the WSOC in study period was closely related to combustion related sources especially biomass burning [36]. In addition, WSOC exhibited strong correlations with metal species such as As (correlation coefficient as 0.93), Se (0.84), Pb (0.84), Mn (0.88), Fe (0.87), and Zn (0.90), which were widely used as markers for primary and combustion related sources such as coal combustion [64,65], vehicle emission [12,36], and industrial sources [66].…”
Section: Primary Sources Of Wsoc Determined By the Pmf Modelmentioning
confidence: 94%
See 1 more Smart Citation
“…and natural factors comprise sandstorm, volcanic eruptions, forest fire, resuspension of road or soil dust, etc. [40,41]. With regard to meteorological conditions, one consideration is the phenomenon of static wind in the horizontal direction of the atmosphere increases, and there is basically no power source for PM diffusion, which results in more and more suspended PM accumulation.…”
Section: Main Causes Of Hw Formationmentioning
confidence: 99%
“…However, a major shortcoming in these instruments is the lack or limited species from field measurements. To obtain more comprehensive information on chemical species in PM2.5, some previous studies have employed several online instruments to simultaneously measure the organic carbon, element carbon, important elements, and water-soluble inorganic ions in PM2.5 (Gao et al, 2016;Peng et al, 2016b;Wang et al, 2018;Huang et al, 2019;Liu et al, 2019). Although major species of PM2.5 have been measured in these research studies, the sum concentration of all the determined species was not close to the PM2.5 mass concentrations, which was partly because OM has not been measured, which is required to measure PM2.5 mass closure (Hand et al, 2011;Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%